Anaemia among Indian children: A study of prevalence and associated factors among 5–9 years old. (December 2020) - Rahman, Mohammad Hifz Ur; Chauhan, Shekhar; Patel, Ratna; Boro, Bandita; Anwar, Tarique; Kumar, Pradeep; Muhammad, T.; Srivastava, Shobhit
Highlights: Children with a low level of folate, zinc, and vitamin A were more likely to have anaemia. Children aged 5–7 years were more likely to have anaemia than children aged 8–9 years of age. Anaemia was lower in the Southern region and higher in the Eastern and North-eastern regions. Child's, mother's, and household's characteristics were found to be associated with anaemia. Anaemia among children requires investments in mother's education and socioeconomic status. Abstract: Despite a plethora of research on anaemia among children in India and worldwide, progress has been snail-paced. Most of the studies in India related to anaemia among children are related to children aged 6–59 months. Therefore, this study intends to examine anaemia among children aged 5–9 years of age using a recent nationally representative sample survey 'Comprehensive National Nutrition Survey (CNNS).' CNNS is a cross-sectional, household face to face survey. The total sample size for this study was 14, 664 children who had anaemia. Anaemia among children aged 5–9 was the outcome variable for this study. The anemia level among children was categorized as 1 if haemoglobin level less than 11.5 g/dl (anemic) and 0 otherwise. The explanatory variables were categorized into three groups indicating children's characteristics, maternal characteristics, and household's characteristics. The binary logistic regression analysis had been performed to find out the predictors of anaemia among children aged 5–9 years in India. Nearly one-fourth (23.1%) and one-fifth (21.1%) of the children with low level of Vitamin A and Vitamin B12 were anaemic.. Nearly one-fourth of the children (23.5) aged 5–9 years in India had anaemia The prevalence of anaemia among children was as low as 3.1 percent in Kerala and as high as 41.1 percent in Tripura. The results confirmed that a low level of folate, zinc, and vitamin A were associated with a high level of anaemia among children. Higher mother's education status was accompanied by a low level of anaemia among children. The alarming level of anaemia among children calls for immediate attention in terms of detailed study of risk factors, effective policy, and timely intervention. Anaemia among children aged 5–9 years requires investments in mother's education and socioeconomic status along with improvements in micronutrient intake and overall nutritional wellbeing of the children.